The conceptual model of supply chain risk, green supply chain management practices and organizational performance among malaysian manufacturing sector / Norzawani Ibrahim ... [et al.] - Ibrahim, Norazwani; Abdul Wahab, Mohd Hafeez Al Amin; Zainuddin, Ahmad Zuhairi; Mohd Masdek, Nik Rozila; Abd Rahim, Nur Najjah (2018)
The manufacturing sector has recently looked for organisational performance outcomes concerning economic and environmental performance to provide a competitive edge. Economic performance is perceived as a long-run objective for the organisation, whereas environmental performance supports the success of economic performance. However, the existence of the supply chain risks will be affected both economic and environmental performance. Therefore, organisations need to discover an appropriate strategy to reduce the supply chain risks and improve organisational performance. The principal objective of this study is to perform a conceptual model to examine the mediating role of GSCM practices on the relationship between supply chain risks and organisational performance. This study also proposes the hypotheses as a guide and direction to achieve the objective. The originality of this study is on its investigation of the relationship among supply chain risks, green supply chain management practices, and organisational performance simultaneously, which has not been noticed among previous scholars. This conceptual framework is expected to be used by the Malaysian manufacturing sector to improve organisational performance since this sector is the highest contributor to the Malaysian gross domestic product.